1990
DOI: 10.1128/aac.34.6.1220
|View full text |Cite
|
Sign up to set email alerts
|

Lipoteichoic acid as a new target for activity of antibiotics: mode of action of daptomycin (LY146032)

Abstract: Daptomycin at the MIC allowed the cell mass increase of enterococcal strains and Bacilus subtilis to continue for 2 to 3 h at rates comparable to those of the controls. During this time the cell shape of the former changed to a rod configuration and that of the latter changed to long rods. In these bacteria, in which cell mass continued to increase, the MIC of daptomycin inhibited peptidoglycan synthesis by no more than 20% after 20 min of incubation and by roughly 50% after 2 h of incubation. Other macromolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 36 publications
2
102
0
1
Order By: Relevance
“…58 Cell fractionation experiments detected daptomycin bound to cell walls and cell membranes, but not to cytosolic constituents. 59 The latter study also reported that daptomycin inhibits the biosynthesis of cell wall macromolecules, and the authors proposed inhibition of lipoteichoic acid biosynthesis as daptomycin's major mode of action. Several studies have attempted to determine whether daptomycin indeed directly blocks some enzyme or substrate in cell wall biosynthesis, or alternatively, inhibition of macromolecular synthesis occurs downstream of membrane permeabilization and loss of key metabolites; this question remains controversial (see section 11).…”
Section: Cellular Sites Of Actionmentioning
confidence: 95%
See 3 more Smart Citations
“…58 Cell fractionation experiments detected daptomycin bound to cell walls and cell membranes, but not to cytosolic constituents. 59 The latter study also reported that daptomycin inhibits the biosynthesis of cell wall macromolecules, and the authors proposed inhibition of lipoteichoic acid biosynthesis as daptomycin's major mode of action. Several studies have attempted to determine whether daptomycin indeed directly blocks some enzyme or substrate in cell wall biosynthesis, or alternatively, inhibition of macromolecular synthesis occurs downstream of membrane permeabilization and loss of key metabolites; this question remains controversial (see section 11).…”
Section: Cellular Sites Of Actionmentioning
confidence: 95%
“…Elongated forms of Enterococcus and Bacillus cereus cells grown at MIC were reported in early studies. 59 Bacillus subtilis cells grown with daptomycin at below MIC appeared bent and elongated. 72 While elongated cell forms suggest that division is inhibited, the observation of additional, aberrant septa in Staphylococcus aureus 76 could mean that cell division may be dysregulated rather than disrupted.…”
Section: Effects On Cell Division and Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…The possible bactericidal mechanisms of daptomycin have been exhaustively investigated, especially the interactions between daptomycin and lipid membranes (Canepari et al, 1990;Silverman et al, 2001). It was reported that daptomycin-induced membrane permeabilization and depolarization, finally destroying the bacterial cell membrane, resulting in release of cellular contents (Canepari et al, 1990;Silverman et al, 2001).…”
Section: Discussionmentioning
confidence: 99%